Perilaku Pembelian Impulsif di Marketplace Shopee Pada Mahasiswa Manajemen Universitas Buana Perjuangan Karawang - Aeni, Naura Nur; Suherman, Enjang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Inseparable from the importance of the internet as a communication tool, advances in communication and information technology have occurred rapidly. Since the marketplace offers a place to sell online, sellers don't need to worry when selling online. Students are also influenced by the increasingly widespread phenomenon of hedonic lifestyles. Not all hedonistic students come from upper-class families, so their lifestyle has certain characteristics. This study explores the hedonism and lifestyle of Buana Perjuangan University students when using the Marketplace Marketplace. The method used is qualitative, using interviews and observations of several students. The research results show that the hedonism and active lifestyle of Buana Perjuangan University Karawang students greatly influences their shopping behavior at Shopee. Students who have an active and hedonistic lifestyle tend to buy things more often and make impulse purchases.